Performance of foamed concrete by using by product material : palm oil clinker crushed (POCC) as sand replacement - Chandran, Surendren (2010)
An experimental programmed on foamed concrete and palm oil clinker crushed (P0CC) aggregates is presented. Foam concrete also known as aerated concrete because concrete that produced by using cement combined with fine sand and foam. Significant amount of wastes are generated from palm oil mills which constitutes nuisance to the environment. These wastes if used as aggregate in concrete will serve to sanitise the environment and creates cheaper,' renewable aggregates for construction purposes. (P0CC) which is abundantly available has the potential as a replacement for sand in the production of foamed concrete. This study investigates the effect of replacement of palm oil clinker crushed towards the mechanical properties of foamed concrete. The aim of this research is to determine the compressive strength and elastic modulus of foamed concrete with density of kg/M3 with various percentages of (P0CC). The mix proportion ratio was used through this research is 2:1:1 consists of cement to sand to water. Four types of mix design were prepared with the constant w/c of 0.50 and P0CC content of 0%, 10% and 15% by the total sand respectively. Air curing (natural environmental) was considered at age of 7, 28 and 60 days. The higher compressive strength achieved through the percentage of addition of P0CC increased due to days. It is revealed that the compressive strength of foamed concrete increased significantly. When the percentage of P0CC replaced with sand increase, the strength of samples was increased significantly. The modulus of elastic was increased constantly increasing the percentage of P0CC due to curing days. This study indicates that foamed concrete with P0CC content can be utilized as lightweight concrete.